TEKNOLOGI DOMESTIKASI IKAN TAPAH DI DESA TANAH BAWAH KABUPATEN BANGKA - Khoirul Muslih; Indra Ambalika Syari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2016)
Tapah fish (Wallago leerii), one of Bangka's local fish species found only along the Jeruk River in Tanah Bawah Village, is now threatened with extinction due to fishing pressure and ecological pressure caused by human activities. Moreover, the trend of environmental degradation due to the rampant tin mining on Bangka Island is feared to threaten the original habitat of tapah fish. Tapah fish is one of the most economically important fish because it is not only very popular with the public due to its large size, good taste and savory, but also because of its nutritional value and high price. So far, the supply of tapah fish has only been obtained from natural catches. If this is done continuously due to higher demand, it will threaten the sustainability and even extinction of tapah fish. This condition will also have an impact on the economy of people who depend on river fish catches, especially tapah fish. Proper management of tapah fisheries is needed so that its utilization can be sustainable and optimal and sustainable, one of which is through domestication efforts. This Ipteks for Communities (IbM) program tries to introduce a simple domestication technology that has been tested in the waters of the Kampar River in Riau. The activity begins with rearing tapah fish fry from nature and then enlarging them to a consumable size. Proper maintenance techniques include acclimatization techniques, selecting the right type and dose of feed to stimulate growth and monitoring the water quality of the cultivation container.